Enrichment, Isolation, and Cultural Characteristics of Marine Strains of Clostridium botulinum Type C - Segner, W. P. (1971)
Terrestrial strains of Clostridium botulinum type C, designated 468 and 571, were used to screen various media for growth and sporulation at 30 C. Of the various formulations tested, only egg meat medium fortified with 1% additions of yeast extract, ammonium sulfate, and glucose (FEM medium) gave good growth and satisfactory sporulation. FEM medium was used to recover four marine type C isolates from inshore sediments collected along the Atlantic, the Gulf of Mexico, and the Pacific coasts of the United States. The isolation techniques involved repeated transfer of cultures showing type C toxin in FEM medium and purification by a deep tube method. The medium used for purification was beef infusion-agar supplemented with 0.14% sodium bicarbonate and 0.1% l-cysteine hydrochloride. l-Cysteine was adopted in preference to sodium thioglycolate, because some lots of the latter were definitely inhibitory for growth. The addition of bicarbonate markedly increased viable spore counts of both the marine and terrestrial strains. Various cultural and biochemical characteristics of the marine and the terrestrial strains were compared. With the exception of some variations in their fermentation patterns, both groups showed similar characteristics. Of 23 fermentable compounds tested, the terrestrial strains attacked only glucose and mannose. The marine strains fermented glucose, mannose, galactose, and ribose actively; dextrin, inositol, maltose, and melibiose were weakly fermented.